Giant circumferential esophageal leiomyoma successfully treated by thoracoscopic enucleation with the patient in a prone position: A case report. Issue 3 (14th December 2020) - Higuchi, Tadashi; Koyanagi, Kazuo; Ozawa, Soji; Ninomiya, Yamato; Yatabe, Kentaro; Yamamoto, Miho
Abstract: Esophageal leiomyomas are common benign tumors. Although surgical resection is warranted in symptomatic patients, the procedure used to enucleate a giant, circumferential tumor is complicated. A 38‐year‐old man was referred to our institution with a diagnosis of submucosal esophageal tumor. An endoscopic examination revealed a protruding submucosal mass in the lower third of the esophagus. Computed tomography scans demonstrated a circumferential mass measuring 90 × 40 mm. Examination of the biopsy specimens resulted in a diagnosis of leiomyoma of the esophagus, and thoracoscopic enucleation of the tumor via the right thorax with the patient in the prone position was planned. Histopathological and immunohistochemical staining of the surgical specimen confirmed the preoperative diagnosis of benign leiomyoma. The patient was discharged on postoperative day 7 without any complications.